ADIDAS’S MARKETING COMMUNICATION STRATEGY AMID THE INTERNATIONAL CONFLICT - Yudha, Reza Praditya; Hakim, A. Rahman (Journal of Digital Media Communication, 2025)
The Israel-Palestine conflict represents a geopolitical issue with far-reaching implications for global business, including the brand image of international corporations such as Adidas. Amid growing consumer awareness of sociopolitical issues, corporate responses to the conflict have become a focal point that influences public perception and purchasing decisions. This journal aims to analyze Adidas’s marketing communication strategy in responding to public pressure and boycott movements stemming from its associations with Israeli entities. The study employs a qualitative approach using a case study method. Data were collected through media analysis, official press releases from Adidas, and social media posts by activists and the public. Triangulation techniques were used to ensure data validity by cross-referencing multiple sources. The findings reveal that Adidas adopted a communication strategy characterized by neutrality, avoiding explicit affiliation with either side in the Israel-Palestine conflict. While the company terminated its sponsorship with the Israel Football Association following public pressure, it maintained business ties with Israeli manufacturers. Adidas's communication strategy emphasizes values of diversity, inclusivity, and social responsibility through digital campaigns and humanitarian programs. The discussion suggests that this approach may help minimize reputational damage in the global market, although it does not entirely eliminate boycott threats. In conclusion, Adidas’s communication strategy reflects an effort to balance business continuity and social values amid geopolitical tensions. A neutral yet responsive digital communication approach emerges as key to maintaining brand image and consumer loyalty on a global scale.